IoT-based Smart Baby Swing with an Android Mobile Application - Ganasan, Nanthakumar; Zainal, Nurfarina (Evolution in Electrical and Electronic Engineering, 2023)
Female employment has increased considerably in developed countries in recent years, influencing newborn care in many families. The careless and busy working environment raises the number of milk-choking incidents and Sudden Infant Death Syndrome (SIDS). At present, an automated swing has a restricted swing speed function, and the system is always turned on. It also lacks a real-time monitoring mechanism. To solve these problems, an IoT-based smart baby swing that works in parallel with an Android mobile application was developed in this project. The smart baby swing system consists of hardware devices such as ESP8266 NodeMCU microcontroller, sound sensor, Wi-Fi camera, motor, Blynk cloud server, and internet. The graphical user interface (GUI) layout for the Android Mobile application was designed using Blynk, and the Arduino IDE program is used to control the hardware part. This smart baby swing can control and monitor the baby swing via a smartphone that has a selection of speeds and delay mode functions. It also equips with an alert and push notification to the user when the system senses a baby crying at the sound between 80 and 100 decibels. The ESP32 camera is used to live stream the baby's condition, hence allowing users to monitor the baby in real time. Thus, this smart baby swing can potentially minimise milk-choking and SIDS issues.